Efficacy and safety of an inactivated virus-particle vaccine for SARS-CoV-2, BIV1-CovIran: randomised, placebo controlled, double blind, multicentre, phase 3 clinical trial - Minoo Mohraz; Katayoun Vahdat; Seyyed-Hadi Ghamari; Mohsen Abbasi-Kangevari; Erfan Ghasemi; Yasaman Ghabdian; Negar Rezaei; Maryam Amini Pouya; Asghar Abdoli; Mohammad-Reza Malekpour; Keyvan Koohgir; Sahar Saeedi Moghaddam; et al. (The BMJ, 2023)
To report the efficacy, safety, and exploratory immunogenicity findings of two 5 µg doses of the BIV1-CovIran vaccine. Randomised, placebo controlled, double blind, multicentre, phase 3 clinical trial. In six cities of Iran, including Bushehr, Isfahan, Karaj, Mashhad, Shiraz, and Tehran. The first vaccine or placebo injection of the first participant was on 16 May 2021 in Tehran. The last vaccine or placebo injection of the last participant occurred on 15 July 2021 in Isfahan. 200.167em000 participants aged 18-75 years were randomly assigned to the intervention or placebo groups with a ratio of 2:1. 5 µg vaccine or placebo with the interval of 28 days. Vaccine efficacy for a 90 day follow-up period, safety and explanatory immunogenicity assessment, and variant detection during the trial. 200.167em000 participants were recruited and randomly assigned to receive BIV1-CovIran (n=130.167em335 (66.7%)) or placebo (n=6665 (33.3%)). Participants' mean age was 38.3 (standard deviation 11.2) years, and 6913 (34.6%) were female. Among vaccinated participants that had covid-19 reported during the follow-up (median 83 days), 758 (5.9%) had symptoms, 144 (1.1%) had severe infection, and seven (0.1%) were critical. Among participants who received placebo during the follow-up, 688 (10.7%) had symptoms, 221 (3.4%) had severe infection, and 19 (0.3%) were critical. Overall efficacy was 50.2% (95% confidence interval 44.7% to 55.0%) against symptomatic covid-19, 70.5% (63.7% to 76.1%) against severe disease, and 83.1% (61.2% to 93.5%) against critical cases. Two deaths were reported in the efficacy population in the placebo group, no deaths were from the intervention group. During follow-up, 410.167em922 adverse events were reported: 280.167em782 (68.7%) were adverse reactions, of which 190.167em363 (67.3%) were in the intervention group. Most adverse reactions were mild or moderate in severity (grade 1 or 2) and self-limiting. No serious adverse events were related to the injections. For variant investigation, of 119 participants positive for the SARS-CoV-2 variant, 106 (89.1%) were positive for the delta variant. A two dose regimen of the BIV1-CovIran vaccine conferred efficacy of 50.2% against symptomatic covid-19, 70.5% against severe disease, and 83.1% against critical disease. Vaccination was well tolerated, with no safety concerns raised. Iranian Registry of Clinical Trials, IRCT20201202049567N3. Shifa-Pharmed Industrial Group.
Keywords: 330